functions

Level pending

If f ( x ) = x 2 + 3 f(x)= x^2 + 3 , find the function g g such that g f ( x ) = 2 x 2 + 3 g\circ f(x)= 2x^2 + 3 .

g(x) = 2x - 3 g(x) = 3x - 6 g(x) = 4 - x g(x) = x+ 2

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Finn Hulse
Apr 13, 2014

Let's set it up: g ( 2 x 2 + 3 ) g(2x^2+3) . For the coefficient of x 2 x^2 to go from one to two, we have to have multiplied by two in g ( x ) g(x) . Plugging f ( x ) f(x) into g ( x ) = 2 x g(x)=2x produces 2 x 2 + 6 2x^2+6 , which is three more than the desired. Thus, g ( x ) g(x) must be 2 x 3 \boxed{2x-3} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...